2016
DOI: 10.3168/jds.2015-10462
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the diacylglycerol o-acyltransferase 1 (DGAT1) K232A polymorphism on fatty acid, protein, and mineral composition of dairy cattle milk

Abstract: Several studies have described associations between the diacylglycerol o-acyltransferase 1 (DGAT1) K232A polymorphism and routinely collected milk production traits but not much is known about effects of the DGAT1 polymorphism on detailed milk composition. The aim of this study was to estimate effects of the DGAT1 polymorphism on milk fatty acid, protein, and mineral composition. We looked for effects that were significant and consistent in Danish Holstein Friesian (HF), Danish Jersey, and Dutch HF as these ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 42 publications
4
48
2
2
Order By: Relevance
“…The contribution of DGAT1 K232A polymorphism to the variation in specific isoforms in Dutch Holstein Friesian seems similar to the contribution of QTL2 on BTA1, suggesting a similar mode of action. This is in line with Bovenhuis et al (2016), who showed that DGAT1 might affect the distribution of phosphorus between casein micelles and milk serum.…”
Section: Bta14supporting
confidence: 91%
See 1 more Smart Citation
“…The contribution of DGAT1 K232A polymorphism to the variation in specific isoforms in Dutch Holstein Friesian seems similar to the contribution of QTL2 on BTA1, suggesting a similar mode of action. This is in line with Bovenhuis et al (2016), who showed that DGAT1 might affect the distribution of phosphorus between casein micelles and milk serum.…”
Section: Bta14supporting
confidence: 91%
“…Furthermore, DGAT1 does not affect α S1 -CN-8P concentration (Bijl et al, 2014) and α S2 -CN-12P concentration (this study) at the genomewide significance level. Bovenhuis et al (2016) showed that DGAT1 affects α S2 -CN concentration in Dutch Holstein Friesian and Danish Holstein Friesian; the K allele was associated with higher α S2 -CN concentration. We showed that the increase of α S2 -CN concentration was due to the increase of α S2 -CN-10P and α S2 -CN-11P concentrations in Dutch Holstein Friesian.…”
Section: Bta14mentioning
confidence: 99%
“…These results are largely in agreement with data in the literature. According to Schennink et al (2007), Van Arendonk et al (2009, Duchemin et al (2013), and Bovenhuis et al (2016), the DGAT1 K allele is associated with a larger fraction of C16:0, and smaller fractions of C14:0 (also reported by Lu et al, 2015), and C18 UFA in milk. In addition, Duchemin et al (2013) reported an increase in milk C14:1 cis-9, C16:1 cis-9, and total SFA, and a decrease in total milk UFA for the DGAT1 K allele.…”
Section: Lactation Performance and Milk Fatty Acid Profilementioning
confidence: 92%
“…In addition, Duchemin et al (2013) reported an increase in milk C14:1 cis-9, C16:1 cis-9, and total SFA, and a decrease in total milk UFA for the DGAT1 K allele. Furthermore, according to Van Arendonk et al 2009, Lu et al (2015), and Bovenhuis et al (2016), the DGAT1 K allele is associated with increased contents of C15:0 and C17:0 in milk.…”
Section: Lactation Performance and Milk Fatty Acid Profilementioning
confidence: 95%
“…In the separate analysis with the Dutch samples, significant associations were also detected with these traits, except C14:1. Previous studies have shown that the K allele of DGAT1 polymorphisms has a reducing effect in C14:0 (Schennink et al, 2008;Bovenhuis et al, 2016). Through reduction of C14:0, DGAT1 is also expected to affect the concentrations (%wt/wt) of C14:1.…”
Section: Detection Of Genomic Regions Under the Different Scenariosmentioning
confidence: 98%